BRIEF STRATEGIC FAMILY THERAPY KELUARGA “TT” TERHADAP INTERAKSI SOSIAL “CA” - Rakhmania, Dewi Fitri (Sekolah Tinggi Kesejahteraan Sosial (STKS) Bandung, 2015)
Abstract This article based on result of the research regarding application of Brief Strategic Family Therapy (BSFT) to the